Geoinformation for Informed Decisions - Abdul Rahman, Alias.; Abdul Rahman, Alias.; Boguslawski, Pawel.; Boguslawski, Pawel.; Anton, François.; Anton, François.; Said, Mohamad Nor.; Said, Mohamad Nor.; Omar, Kamaludin Mohd.; Omar, Kamaludin Mohd. (Lecture Notes in Geoinformation and Cartography,, 2014)
This book presents the latest research developments in geoinformation science, which includes all the sub-disciplines of the field, such as: geomatic engineering, GIS, remote sensing, digital photogrammetry, digital cartography, etc.